(3TQM OjhGf Pi GdQeIs - (3Ph GdQeI , CHh GdMGQK ZjdGf Hf YbHI Hf fgjS Hf eSYhO GdYOhj, CHh GdMGQK,J (B117 (3g` s
(3ChdgG (B:s
(3SjdG ef GdOYU GZTJg eYGQagG fcHGA JSMH CYdGg ajfSMH s
(3BNQgG (B:s
(3EPG GLJdOhG HeYJQc bjGekG Ydi GdTYK GdYhGHS Ch fRGdG s
(3Pi GdQeg gh CHh GdMGQK ZjdGf Hf YbHgs
(3GdeJhai (B117 (3g`s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B319 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B44s
Keywords: (3GdCOHs